Pengaruh Tekanan, Kesempatan, Rasionalisasi dan Kemampuan Terhadap Tindakan Kecurangan (Fraud) - Mulya, Dea An-nisa Try; Syofyan, Efrizal (Universitas Negeri Padang, 2025)
This study was conducted at Class II A Correctional Institution and Class II B Detention Center in Padang City by involving prisoners of corruption as research subjects. The purpose of this study is to examine the variables that affect fraud according to pressure, opportunity, rationalization, and ability. The research method used is causative research with total sampling on 50 prisoners. Information was gathered via a survey with a Likert scale and processed using multiple regression analysis with Adjusted R2. The findings indicated that opportunity, rationalization, and lying ability have a significant influence on fraud, while pressure has no significant effect. Suggestions include expanding the scope of external auditor examinations, developing research variables, and using more varied data collection methods for future research. It is expected that this research will give different linked parties a better knowledge of the factors that drive fraud.